ANALISIS PERBANDINGAN BIAYA DAN WAKTU PEKERJAAN STRUKTUR PELAT LANTAI DENGAN MENGGUNAKAN BETON BERTULANG - Perdana, Anandika Arga Perdana; Abdul Rokhman (Jurnal Sipil Krisna, 2023)
Land clearing with the aim of opening new residential areas is one way to reduce population density in Jakarta. One of them is the Development Area in North Jakarta as a place to build a multi-storey building with a reinforced concrete structure, one of the jobs that has an influence on cost and time is the floor slab with the right method will make construction more efficient. The half slab precast method is able to make the duration of work shorter than conventional methods and prevent project delays. This case study compares the cost and time of the two methods on the 3rd floor with the aim of determining which method is more efficient. It was found that the half slab precast method is more efficient because there is a cost difference of Rp3,711,284,049.00 and a time difference of 19.93 days